Stromal vascular fraction inhibits renal fibrosis by regulating metabolism and inflammation in obstructive nephropathy - Yue, Guang; Yang, Yunjie; Jia, Hongshuai; Wu, Yangyang; Ma, Lifei; Yi, Xiaoyu; Tao, Yuandong; Zhou, Huixia (Frontiers in Pharmacology, 2025)
Obstructive nephropathy is one of the leading causes of kidney injury and fibrosis, which can lead to end-stage renal disease (ESRD). Stromal vascular fraction (SVF), a heterogeneous cell mixture derived from adipose tissue, has been widely used for regenerative medicine across many preclinical models and clinical applications. Recent studies have suggested that SVF can alleviate acute kidney injury in mice. However, to our knowledge, the therapeutic effects of SVF on obstructive nephropathy have not been studied before. In this study, we evaluated the therapeutic potential of SVF on obstructive nephropathy in mice with unilateral ureteral obstruction (UUO). We revealed that autologous SVF administration mitigated UUO-induced renal fibrosis. SVF treatment inhibited both the infiltration of neutrophils and CD4+ T cells, as well as the production of inflammatory cytokines. Moreover, SVF promoted metabolic reprogramming and improved mitochondrial function in the obstructed kidneys, partially through PPAR pathway activation. Mechanistically, SVF-mediated PPAR activation inhibited the epithelial-mesenchymal transition (EMT) process of tubular cells, thus alleviating renal fibrosis in UUO mice. We further confirmed that pharmacological activation of PPAR pathway significantly reduced fibrosis in UUO kidneys. Therefore, our study suggests that SVF may represent a promising therapeutic strategy for obstructive nephropathy.